Kecerdasan Buatan (AI) dan Martabat Manusia: Tinjauan Etika Katolik - Agustinus Abraham (Tri Tunggal: Jurnal Pendidikan Kristen dan Katolik, 2026)
This study examines artificial intelligence (AI) and its implications for human dignity from the perspective of Catholic ethics. The rapid development of AI has brought significant benefits in various fields, such as education, healthcare, communication, and economics. However, AI also raises ethical concerns, including privacy violations, algorithmic bias, manipulation of information, automation-driven unemployment, and the reduction of human beings into mere digital data. This research employs a qualitative method with a literature study approach by analyzing books, scientific journals, and official documents of the Catholic Church related to AI and human dignity. The findings reveal that the Catholic Church does not reject technological advancement but emphasizes that AI must remain human-centered and oriented toward the common good. In Catholic theology, human beings possess inherent dignity because they are created in the image of God (imago Dei), and therefore cannot be replaced or reduced by technology. Catholic ethics provides moral principles such as human dignity, solidarity, justice, transparency, and moral responsibility as foundations for the responsible use of AI. Consequently, AI should function as a tool that serves humanity and supports integral human development rather than becoming an instrument of domination and dehumanization.